The impact of low-dose aspirin in the Brain Injury Guidelines on outcomes in traumatic brain injury: A retrospective cohort study. Issue 2 (24th February 2023) - Webb, Andrew J.; Oetken, Heath J.; Plott, A. Joseph; Knapp, Christopher; Munger, Daniel N.; Gibson, Erica; Schreiber, Martin; Barton, Cassie A.
Abstract : In this retrospective cohort study, patients with traumatic intracranial hemorrhage who would have qualified as Brain Injury Guidelines class 1 if not for low dose aspirin use experienced in-hospital mortality or need for neurosurgery at similar rates to other BIG 1 patients. Abstract : BACKGROUND: Current Brain Injury Guidelines (BIG) characterize patients with intracranial hemorrhage taking antiplatelet or anticoagulant agents as BIG 3 (the most severe category) regardless of trauma severity. This study assessed the risk of in-hospital mortality or need for neurosurgery in patients taking low-dose aspirin who otherwise would be classified as BIG 1. METHODS: This was a retrospective study at an academic level 1 trauma center. Patients were included if they were admitted with traumatic intracerebral hemorrhage and were evaluated by the BIG criteria. Exclusion criteria included indeterminate BIG status or patients with missing primary outcomes documentation. Patients were categorized as BIG 1, BIG 2, BIG 3, or BIG 1 on aspirin (patients with BIG 1 features taking low-dose aspirin). The primary endpoint was a composite of neurosurgical intervention and all-cause in-hospital mortality. Key secondary endpoints include rate of intracranial hemorrhage progression, and intensive care unit– and hospital-free days. RESULTS: A total of 1, 520 patients met the inclusion criteria. Median initial Glasgow Coma Scale was 14 (interquartile range [IQR], 12–15), Injury Severity Scale score was 17 (IQR, 10–25), and Abbreviated Injury Scale subscore head and neck (AISHead ) was 3 (IQR, 3–4). The rate of the primary outcome for BIG 1, BIG 1 on aspirin, BIG 2, and BIG 3 was 1%, 2.2%, 1%, and 27%, respectively; the difference between BIG 1 on aspirin and BIG 3 was significant ( p < 0.001). CONCLUSION: Patients taking low-dose aspirin with otherwise BIG 1–grade injuries experienced mortality and required neurosurgery significantly less often than other patients categorized as BIG 3. Inclusion of low-dose aspirin in the BIG criteria should be reevaluated. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level IV. Abstract :